Health Promotion Interventions in Occupational Settings: Fact-finding Survey among Italian Occupational Physicians - Leso, Veruscka; Coggiola, Maurizio; Pira, Enrico; Pollone, Alberto; Simonini, Silvia; Talini, Donatella; Spatari, Giovanna; Iavicoli, Ivo (La Medicina del Lavoro, 2023)
Background: Occupational Physicians (OPs) are essential for health promotion (HP) at the workplace, although their HP knowledge and perception are still under-searched. Methods: Between September and December 2022, the Italian Society of Occupational Medicine (SIML) – HP working group performed a cross-sectional survey on SIML-OPs aimed to address their approach, experience, strategies, and needs concerning HP plans.Results: A total of 336 OPs completed the questionnaire. Regarding HP’s OP perception, this was reported as a social investment (34.45%) and shared responsibility for all the company’s preventive figures (30.18%). Over half of the enrolled OPs declared to have been involved as HP plans’ organizers (57.30%) or collaborators (54.80%) in the previous 5 years. The greatest percentage of organizers were in the younger age groups (40-59 years; 50%). Additionally, following a more limited number of companies, prevalently of medium-high dimensions, and more than 500 workers were positively associated with greater OP participation in HP initiatives. Promoting healthy lifestyles was the main target of the HP plans (88.64%). Interdisciplinary collaboration, OP training on HP procedures and information on the targeted population have been reported as effective issues to support an active engagement of OPs in HP. Conclusions: A general interest of the Italian OPs with respect to HP was demonstrated, however, information on the potential benefits of HP in workplace aligned with OP perceptions and needs seem necessary to successfully implement HP interventions.